Genetic variability and association studies in Sunflower Inbreds: Genetic variability and association studies in Sunflower Inbreds - S NEELIMA; K VENKATARAMANAMMA; K PRABHAKAR; N C VENKATESWARLU (Journal of Oilseeds Research, 2023)
Genetic variability, heritability, genetic advance and association studies were carried out in 87 sunflower inbreds shared by different AICRP centres for six yield and its contributing traits. Results of ANOVA showed highly significant mean sum of squares for all the traits indicating presence of sufficient variability in the experimental material. Wide range of variation was noticed in plant height followed by seed yield and days to 50 % flowering. High phenotypic and genotypic coefficient of variation were recorded for head diameter, seed yield per plant and 100 seed weight. High heritability coupled with high genetic advance as per cent of mean was exhibited for seed yield indicated directional selection could be effective. Head diameter recorded strong correlation with seed yield followed by plant height and 100 seed weight and in turn these traits were also strongly intercorrelated.